Análise da indústria ervateira da região Sudoeste do Paraná, por meio dos arranjos produtivos locais - Teixeira, Alexandre Marinho (2006)
The general objective of this work is to analyze the industrial sector of the Mate crop of the Southwest region of Paraná State. Analysis was performed through the value of the local productive arrangements and clusters, identifying their characteristics and specificity, links of partnerships and application of the concepts in the researched area. The mentioned area concentrates approximately 30% of the whole Mate crop industry of the State, corroborating with the concept of local productive arrangements. The research was accomplished among small, medium and big companies based in the region and members of FIEP (Federation of the Industries and Companies of the State of Paraná). The scale of Likert was used as the tool of measurement in order to identify the intensity degree of the actions used by the industries, such as the relationship level among the agents of a possible productive arrangement place. This work mentions, respectively, the history, the main approaches, interpretative chain and typologies of local productive arrangements and of clusters. As for the Mate crop industrial sector it portrays the extrativism in Brazil, the history, its uses, characteristics and improvement process, commercial movements and of the mate production. It makes an analysis, considerations and suggestions to contribute to the economical growth and development of the industrial Mate sector of the Southwest region of Paraná